Narsarsukite Na2TiOSi4O10 as a low voltage silicate anode for rechargeable Li-ion and Na-ion batteries - Chaupatnaik, Anshuman (2020)
Phase-pure Narsarsukite Na2TiOSi4O10, prepared by solid-state reaction, was found to reversibly (de)intercalate one lithium by utilizing the Ti(IV)/Ti(III) redox couple. Registering a low operational voltage at 0.58 V, it delivered near theoretical capacity of 70 mAh·g-1 at a rate of C/10. Excellent rate performance was observed retaining 42 mAh·g-1 (or 60%) of the theoretical capacity even at a fast rate of 20C. With no electrode optimization, it delivered robust cycling stability by maintaining 80% capacity retention (at a rate of C/2) in the end of 200 cycles. Na2TiOSi4O10 silicate anode involved a (single-phase) solid solution mechanism. Fast lithium (de)insertion without any significant capacity loss can be linked to the rigid endless large tunnels built from the stacked rings of four SiO4 tetrahedra. This silicate material was further found to work as a 0.53 V anode for sodium-ion batteries delivering capacity close to 30 mAh·g-1 (at a rate of C/10). Narsarsukite Na2TiOSi4O10 forms a low voltage silicate anode for secondary Li-ion and Na-ion batteries.